Pengaruh Permainan Tebak Gambar Berbahasa Inggris Terhadap Peningkatan Pengetahuan Pada Siswa Kelas 1 SDN 1 Kawalimukti - Rizki Aulia, Adinda; Azmar, Dwiva; Agustina, Lena; Nurhaliza, Nabila; Salsabilah, Nadwa; Nursamsi, Nursamsi; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
This study investigates the impact of English language guidance through picture guessing games on the development of early childhood, particularly among first-grade students at SDN 1 Kawalimukti. The research methodology employed a pre-experimental design with a one group pre-post test. Evaluation results demonstrate that the guidance activities proceeded as planned with full participation from 26 students. Proficiency in english, especially in vocabulary such as animal names, fruits, letters, and numbers, significantly improved after the guidance. With the support of picture guessing games as a learning medium, children exhibited remarkable progress in speaking and using the english language. In conclusion, this guidance not only enhanced the language skills of the children but also laid a strong foundation for subsequent English language education at an early age. Keywords: early childhood, english language, learning media, picture guessing games.